2013
DOI: 10.1142/s0192415x13500961
|View full text |Cite
|
Sign up to set email alerts
|

Hispolon from Phellinus linteus Induces G0/G1 Cell Cycle Arrest and Apoptosis in NB4 Human Leukaemia Cells

Abstract: Hispolon (a phenolic compound isolated from Phellinus linteus) has been shown to possess strong antioxidant, anti-inflammatory, anticancer, and antidiabetic properties. In this study, we investigated the antiproliferative effect of hispolon on human hepatocellular carcinoma NB4 cells using the MTT assay, DNA fragmentation, DAPI (4, 6-diamidino-2-phenylindole dihydrochloride) staining, and flow cytometric analysis. Hispolon inhibited the cellular growth of NB4 cells in a dose-dependent manner through the induct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 26 publications
0
47
0
Order By: Relevance
“…Several studies have demonstrated that hispolon blocks cell cycle progression at the G0/G1 [12,20] or G2/M [21] phase, which depends on the cell context. Similarly, hispolon inhibits cell cycle progression and induces cell cycle arrest in G0/G1 phase in A549 and H661 cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have demonstrated that hispolon blocks cell cycle progression at the G0/G1 [12,20] or G2/M [21] phase, which depends on the cell context. Similarly, hispolon inhibits cell cycle progression and induces cell cycle arrest in G0/G1 phase in A549 and H661 cells.…”
Section: Discussionmentioning
confidence: 99%
“…To determine the effect of hispolon on the cell viability of nonsmall cell lung cancer cells, A549 or H661 cells were treated with various concentrations of hispolon (0, 5, 10, 20, 40, 80 and 160 lM) for different time periods (12,24, 48 and 72 h). Cells with 0.1% DMSO were served as a control.…”
Section: Hispolon Inhibits the Growth Of A549 And H661 Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study reported that sanghuang has moderate pharmacological activity: it enhances immunity, antitumor, 15,16 antiinammatory, [16][17][18] antioxidant activity; [16][17][18] and hepatoprotective effects; 19 among others. According to a research report, the active compounds in the sanghuang fruiting body include polysaccharides, triterpenoids, pyran and furan ketones, and polyphenolic compounds.…”
Section: -10mentioning
confidence: 99%
“…In addition, HPL has demonstrated antitumor effects in various types of cancer cells, including melanoma, leukemia, hepatocarcinoma, bladder cancer and gastric cancer cells (16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%